Digital Knowledge and Financial Resilience as Determinants of Financial Behavior: Evidence from Indonesia - Amin Hou; Muhammad Restu Razaq; Ibrahim Mallam Fali; Leony Hoki; Prianda Pebri (Yayasan Bina Bisnis Nusantara Medan, 2025)
Financial resilience (FR) and digital knowledge (DK) are two significant things that affect how people behave with money in the digital financial ecosystem, especially in developing nations like Indonesia. This study seeks to examine the mediating function of FR in the correlation between DK and FB among digital financial users in Medan City. This research employs a quantitative methodology, gathering data via an online survey of 230 participants who are active users of digital financial platforms, including e-wallets, mobile banking, and fintech lending. The Partial Least Squares–Structural Equation Modeling (PLS-SEM) method was used to investigate the association between the postulated variables. The findings indicate that DK exerts a favorable and significant influence on both FR and FB, while FR similarly impacts FB positively. Furthermore, FR has been shown to partially moderate the link between DK and FB. This suggests that people who know more about digital technology tend to be better at handling money, which indicates that they are more responsible and healthy with their money. These results corroborate that digital competence enhances access to financial services and fortifies individuals' capacity to manage financial stress and make judicious financial decisions. This work theoretically enhances the behavioral finance literature by emphasizing the significance of incorporating digital literacy and financial resilience as essential factors influencing prudent financial behavior in the digital era. In practice, the findings of this study suggest that governments and financial institutions should develop complete digital financial education programs that emphasize both technical competencies and psychological preparedness to confront contemporary financial difficulties